A cerium oxide material, preparation method and application thereof
By preparing the ceria material with a mixed structure of the ball bat, the problem of poor dispersion of nano ceria in rubber is solved, and the rubber's aging resistance, oxidation resistance and ultraviolet resistance are improved, simplifying the production process and reducing costs.
Patent Information
- Application Number
- CN202411586425.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-08
- Publication Date
- 2025-03-04
- Estimated Expiration
- 2044-11-08
AI Technical Summary
The existing nano ceria has poor dispersion in rubber, resulting in poor anti-aging effects, and the modification treatment increases production costs and environmentally friendly treatment difficulty.
The cerium oxide material with a ball stick mixed structure is used to react cerium salt and a precipitant in aqueous solution to form a precipitate and calcined to prepare a cerium oxide material with a ball stick mixed structure with a micro-nano scale, which is used as a preventive agent in rubber composite materials.
The rubber's aging resistance, oxidation resistance and mechanical properties are improved, the combination of natural rubber and carbon black is enhanced, and the UV resistance of rubber is significantly improved, without modification treatment, simplifying the production process.
Smart Images

Figure CN119080048B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of rare earth metal compound materials, and in particular to a cerium oxide material, a preparation method and application thereof. Background Art
[0002] Rubber has become an indispensable material for national economy and national defense construction due to its unique high elasticity and excellent insulation, air tightness, tensile strength and wear resistance. However, under the influence of external factors such as heat, oxygen and light, the molecular structure of rubber products will change, resulting in poor product performance and even aging phenomena such as crack damage, which puts forward certain aging resistance requirements for rubber. In order to extend the service life of rubber products, it is necessary to add antioxidants to rubber, thereby extending the storage period and service life of rubber and its products.
[0003] Rare earths are known as "industrial vitamins" and have become an extremely important strategic resource. 2 ) has been widely used in luminescent materials, polishing agents, ultraviolet absorbers, automobile exhaust purification catalysts, chemical decolorizers for glass, radiation-resistant glass, electronic ceramics, etc. 2 It has almost no absorption in the visible light range, but has strong absorption capacity for ultraviolet light and is often used as an ultraviolet absorber. At the same time, the 4f electron layer structure of rare earth elements has a large number of empty orbitals and has a strong ability to combine with free radicals. The complexes formed with certain compounds containing O, N, and S atoms have a significant effect in inhibiting long-term thermal oxidation aging of rubber.
[0004] In addition, nano-CeO 2 It can improve the thermal stability of rubber, and the smaller the particle size, the higher the surface activity, and the more obvious the effect of improving the anti-aging performance of rubber. Therefore, nano cerium dioxide is expected to be used as a new generation of efficient, environmentally friendly and safe antioxidant for rubber materials. However, it is precisely because of the small particle size, large specific surface area and high surface activity of nano-cerium oxide that it is very easy to agglomerate and difficult to disperse in rubber. In order to increase the binding force between nano cerium oxide and rubber and improve the dispersion ability of nano particles in rubber, it is often necessary to modify the surface of nano cerium oxide, by reducing the surface energy state of nano particles, eliminating the surface charge of particles, weakening the surface polarity, and improving the affinity between cerium oxide nanoparticles and rubber. Common modifiers include coupling agents and surface modifiers, which increase production costs and technical difficulties. In addition, the harmful substances emitted by modifiers are difficult to degrade, and the cost of environmental protection treatment is high.
[0005] Although there are many methods for preparing ultrafine ceria-based composite oxides, there are still considerable challenges in controlling the morphology and size of the materials and preparing products with uniform particle size, good dispersion, high yield and low cost. 2The preparation methods can be divided into two categories: physical methods and chemical methods. Chemical precipitation is a widely used method for synthesizing high-purity nanoparticles. The chemical precipitation method is simple in experimental operation for preparing nano-cerium dioxide, easy to prepare in large quantities, low in cost, high in economic value, and the prepared nanoparticles are of high purity. However, the powder has poor dispersibility and serious agglomeration, which is a problem for industrial production. Summary of the invention
[0006] In view of this, the object of the present invention is to provide a cerium oxide material, a preparation method and application thereof.
[0007] <First aspect>
[0008] The invention provides a cerium oxide material having a ball-and-rod mixed morphology structure.
[0009] As an embodiment, the particle size of the spherical particles in the cerium oxide material is nanometer-level, and the particle size of the rod-shaped particles is micrometer-level.
[0010] As an embodiment, the spherical particles and the rod-shaped particles are prepared simultaneously during the reaction process.
[0011] As an embodiment, the cerium oxide material is prepared by adopting the above-mentioned method for preparing the cerium oxide material.
[0012] As an embodiment, the short diameter of the rod-shaped particles in the cerium oxide material is in the range of 0.5-3 μm, the long diameter is in the range of 4-10 μm, and the aspect ratio is 1: (2.5-10).
[0013] As an embodiment, the particle size of the spherical particles in the cerium oxide material is 400-800 nm.
[0014] <Second Aspect>
[0015] The invention provides a use of a cerium oxide material with a ball-and-stick hybrid structure. The cerium oxide is applied to the fields of luminescent materials, polishing agents, ultraviolet absorbers, automobile exhaust purification catalysts, chemical decolorizing agents for glass, radiation-resistant glass, electronic ceramics, rubber materials, and the like.
[0016] As an embodiment, the cerium oxide is used as an antioxidant in the field of rubber materials.
[0017] <Third Aspect>
[0018] The present invention provides a method for preparing a cerium oxide material, which is used to prepare the cerium oxide material having a ball-and-stick mixed morphology structure, comprising the following steps:
[0019] The cerium salt and the precipitant are reacted in an aqueous solution environment to generate a precipitate, and the precipitate is extracted and calcined to obtain a cerium oxide material with a ball-and-stick mixed structure.
[0020] As an embodiment, the cerium salt and the precipitant react at room temperature to form a precipitate.
[0021] As an embodiment, no surfactant is added to the precipitate prior to calcination.
[0022] As an embodiment, the cerium salt is a water-soluble cerium salt.
[0023] As an embodiment, the cerium salt includes one or more of cerium nitrate, cerous nitrate, and cerium chloride.
[0024] As an embodiment, the precipitant includes one or more of alkaline substances, amide compounds, organic acids, and organic amines.
[0025] As an embodiment, the alkaline substance is selected to generate OH after dissolving in water. - of substance.
[0026] As an embodiment, the alkaline substance is selected from one or more of carbonates and bicarbonates.
[0027] As an embodiment, the carbonate is selected from one or more of sodium carbonate, potassium carbonate, and ammonium carbonate.
[0028] As an embodiment, the bicarbonate is selected from one or more of sodium bicarbonate, potassium bicarbonate, and ammonium bicarbonate.
[0029] As an embodiment, the organic acid is oxalic acid.
[0030] As an embodiment, the organic amine is triethylenetetramine.
[0031] In some embodiments, the amide compound is urea.
[0032] As an embodiment, the method for preparing the cerium oxide material is to mix the cerium salt aqueous solution and the precipitant aqueous solution, and stir the reaction system by ultrasonic mechanical stirring at room temperature to make the reaction more complete.
[0033] As an embodiment, the rotation speed of the ultrasonic mechanical stirring is 200~1800 r / min.
[0034] In some embodiments, the rotation speed of the ultrasonic mechanical stirring is 1000 r / min.
[0035] As an embodiment, the extraction of the precipitate comprises removing a supernatant by standing the precipitate to obtain the precipitate.
[0036] As an implementation scheme, the standing time is 4 to 12 h.
[0037] As an embodiment, the precipitate is further washed and dried before being calcined.
[0038] As an embodiment, the drying temperature is 50-80°C.
[0039] In some embodiments, the drying temperature is 60°C.
[0040] As an embodiment, the washing treatment is washing with water until neutrality, and then washing with ethanol.
[0041] As an embodiment, the concentration of the cerium salt aqueous solution is 0.1-5.0 M, and the concentration of the precipitant aqueous solution is 0.2-10.0 M.
[0042] In some embodiments, the concentration of the cerium salt aqueous solution is 0.5-1.5 M, and the concentration of the precipitant aqueous solution is 0.5-1.5 M.
[0043] As an embodiment, the molar ratio of the cerium salt to the precipitant is 1: (0.3~5).
[0044] In some embodiments, the molar ratio of the cerium salt to the precipitant is 1: (0.3~2).
[0045] As an embodiment, the calcination treatment is carried out at a temperature of 450-800°C and for a time of 1-2 h.
[0046] In some embodiments, the calcination treatment is carried out at a temperature of 450° C. and for a time of 2 h.
[0047] As an embodiment, the preparation method of the cerium oxide material is to mix a cerium salt aqueous solution and a precipitant aqueous solution, react at room temperature to generate a precipitate, extract, wash and dry the precipitate, and then calcine it at 450~800℃ for 1~2h to obtain a cerium oxide material with a micro-nano scale ball-and-rod hybrid structure.
[0048] <Fourth Aspect>
[0049] The present invention provides a composition of a rubber composite material, comprising a ball-and-bat mixed structure cerium oxide material as an antioxidant, and the composition comprises, by mass:
[0050] Raw rubber: 100 parts, reinforcing agent: 40~70 parts, activator: 4~6 parts, plasticizer: 1~3 parts, dispersant: 0.5~2 parts, accelerator: 1~3 parts, vulcanizer: 1~3 parts, antioxidant: 0.5~10 parts.
[0051] As an embodiment, the raw rubber is one of natural rubber, butyl rubber, styrene-butadiene rubber, brominated butyl rubber, chlorinated butyl rubber, chlorosulfonated polyethylene rubber, nitrile rubber, polyacrylate rubber, chloroprene rubber, silicone rubber, and polysulfide rubber.
[0052] In some embodiments, the raw rubber is natural rubber.
[0053] As an embodiment, the reinforcing agent includes an organic, inorganic or metal oxide filler.
[0054] As an embodiment, the reinforcing agent includes one or more of carbon black, resin, short fiber, lignin, graphene, carbon nanotubes, white carbon, kaolin, and mica flakes.
[0055] In some embodiments, the reinforcing agent is carbon black.
[0056] As one embodiment, the active agent is zinc oxide.
[0057] As an embodiment, the plasticizer includes one or more of vaseline, paraffin, pine tar, and fatty acid.
[0058] In some embodiments, the plasticizer is stearic acid.
[0059] As an embodiment, the dispersant includes one or more of vinyl bisstearamide, octadecylamine, and sodium dodecyl sulfate.
[0060] In some embodiments, the dispersant is vinyl bisstearamide.
[0061] As an embodiment, the accelerator includes one or more of benzothiazole disulfide, N-cyclohexyl-2-benzothiazole sulfenamide, N-oxydiethylene-2-benzothiazole sulfenamide, tetramethylthiuram disulfide, and diphenylguanidine.
[0062] In some embodiments, the accelerator includes benzothiazyl disulfide, N-cyclohexyl-2-benzothiazole sulfenamide.
[0063] In some embodiments, the mass ratio of benzothiazole disulfide to N-cyclohexyl-2-benzothiazole sulfenamide is 1: (1-3).
[0064] As an embodiment, the vulcanizing agent is selected from one of a sulfur vulcanization system, a phenolic resin vulcanization system, a peroxide vulcanization system, a metal oxide vulcanization system, and a maleimide vulcanization system.
[0065] As an embodiment, the vulcanizing agent includes one of sulfur, dicumyl peroxide, phenolic resin, p-benzoquinone dioxime, and maleimide.
[0066] As an embodiment, the phenolic resin is selected from brominated octylphenolic vulcanized resin.
[0067] In some embodiments, the vulcanizing agent is sulfur.
[0068] In some embodiments, the amount of carbon black is 45-65 parts.
[0069] In some embodiments, the amount of stearic acid is 1.5 to 2 parts.
[0070] In some embodiments, the amount of sulfur is 1.5 to 2 parts.
[0071] As an embodiment, the mass fraction of the ball-and-stick hybrid structure cerium oxide in the rubber composite material is 0.5-4%.
[0072] As an embodiment, the mass fraction of the ball-and-stick hybrid structure cerium oxide in the rubber composite material is 1-3%.
[0073] In some embodiments, the mass fraction of the ball-and-bat hybrid structure cerium oxide in the rubber composite material is 1%, 2%, or 3%.
[0074] <Fifth Aspect>
[0075] The present invention provides a method for preparing a rubber composite material, wherein the raw material is a composition of the above-mentioned rubber composite material, and the method comprises the following steps:
[0076] The composition is subjected to a banburying treatment to obtain a banburying rubber;
[0077] The rubber mix is subjected to a thin pass treatment to obtain a rubber mix;
[0078] The rubber compound is subjected to a flat plate hot pressing process to obtain the rubber composite material.
[0079] As an embodiment, the temperature of the banburying treatment is 60-100°C and the time is 12-15 min.
[0080] In some embodiments, the mixing process is carried out at a temperature of 60° C. and for 15 min.
[0081] As an embodiment, the roller distance in the thin pass process is modulated by 1.5 to 2.5 mm.
[0082] In some embodiments, the roller pitch is modulated by 2 mm during the thin pass process.
[0083] As an embodiment, the temperature during the flat plate hot pressing treatment is 140-180°C, the pressure is 10-20 MPa, and the time is 15-30 min.
[0084] In some embodiments, the temperature of the flat plate hot pressing treatment is 140° C., the pressure is 20 MPa, and the time is 30 min.
[0085] Compared with the prior art, the present invention has the following beneficial effects:
[0086] The present invention provides a method for preparing a cerium oxide material. A cerium salt (such as cerium nitrate) and a precipitant (such as urea) are reacted, and the product is calcined to prepare a cerium oxide material with a micro-nano scale ball-rod mixed structure. The chemical precipitation method is simple and fast, does not require a high-pressure environment in a reactor to promote crystallization, and does not require the addition of any structure-directing agent or template agent or crystallization solvent or other surfactant, and is more easily controllable in large quantities, low in cost, and low in energy. The prepared product consists of a certain proportion of spheres and rods with regular morphology and uniform size, has good dispersibility, no obvious agglomeration phenomenon, stable morphology and performance, and excellent repeatability.
[0087] The cerium oxide material provided by the present invention has a large specific surface area, a wide pore structure and excellent electron transport performance, and is suitable for use as a catalyst, a polishing agent and a fuel cell electrolyte material, and is also suitable for use as an ultraviolet absorber (or filler) in rubber and cosmetics.
[0088] The micro-nano scale ball-and-stick hybrid structure cerium oxide material prepared by the present invention is used as a rubber antioxidant. The aging resistance, oxidation resistance and mechanical properties of the rubber can be greatly improved without modifying the cerium oxide material. The bonding performance of natural rubber and carbon black can be effectively enhanced, and the tensile strength and aging resistance of the rubber can be improved. In particular, the anti-ultraviolet performance of the rubber can be significantly improved, and the aging resistance of the rubber products during use can be further improved. BRIEF DESCRIPTION OF THE DRAWINGS
[0089] Other features, objects and advantages of the present invention will become more apparent from the detailed description of non-limiting embodiments made with reference to the following drawings:
[0090] Figure 1 The CeO in Example 1 2 Powder sample picture;
[0091] Figure 2 1 is a characterization diagram of sample C-1 (ball-and-stick mixed state) prepared in Example 1 of the present invention, (a) and (b) are SEM images of sample C-1 at different magnifications;
[0092] Figure 31 is a characterization diagram of sample C-2 (ball-and-stick mixed state) prepared in Example 2 of the present invention, and both (a) and (b) are SEM images of sample C-2 at different magnifications;
[0093] Figure 4 1 is a characterization diagram of sample C-3 (ball-and-stick mixed state) prepared in Example 3 of the present invention, and both (a) and (b) are SEM images of sample C-3 at different magnifications;
[0094] Figure 5 1 is a characterization diagram of sample C-4 (ball-and-stick mixed state) prepared in Example 4 of the present invention, and both (a) and (b) are SEM images of sample C-4 at different magnifications;
[0095] Figure 6 1 is a characterization diagram of sample D-1 (spherical) prepared in comparative example 1 of the present invention, wherein (a) is a SEM image of sample D-1, and (b) is a TEM image of sample D-1;
[0096] Figure 7 1 is a characterization diagram of sample D-2 (rod-shaped) prepared in comparative example 2 of the present invention, wherein (a) is a SEM image of sample D-2, and (b) is a TEM image of sample D-2;
[0097] Figure 8 is a rubber product diagram of Example 5;
[0098] Fig. 9 is a rubber tensile test diagram of Example 5;
[0099] Fig.10 The stress-strain diagrams of Examples 5-9 and Comparative Example 3 before and after aging, wherein (a) is the stress-strain diagram before aging, (b) is the stress-strain diagram after 48 hours of thermal oxygen aging; (c) is the stress-strain diagram after 48 hours of ozone aging; (d) is the stress-strain diagram after 48 hours of ultraviolet aging;
[0100] Fig.11 The stress-strain diagrams of Example 5 and Comparative Examples 4-5 before and after aging, wherein (a) is the stress-strain diagram before aging, (b) is the stress-strain diagram after 48 hours of thermal oxygen aging; (c) is the stress-strain diagram after 48 hours of ozone aging; (d) is the stress-strain diagram after 48 hours of ultraviolet aging;
[0101] Fig.12 3 are thermogravimetric curves of Examples 5-8 and Comparative Example 3, wherein (a) is the TGA curve of the rubber composite material, and (b) is the corresponding DTG curve. DETAILED DESCRIPTION
[0102] The present invention is described in detail below in conjunction with embodiments. The following embodiments will help those skilled in the art to further understand the present invention, but are not intended to limit the present invention in any form. It should be noted that, for those of ordinary skill in the art, some adjustments and improvements can also be made without departing from the concept of the present invention. These all belong to the protection scope of the present invention.
[0103] This specific embodiment first introduces a method for preparing cerium oxide powder. The prepared cerium oxide powder has a micro-nano scale ball-and-rod mixed morphology structure. The preparation method is:
[0104] The cerium salt and the precipitant are reacted in an aqueous solution environment to generate a precipitate, and the precipitate is extracted and calcined to obtain a cerium oxide material with a ball-and-stick mixed structure.
[0105] As an embodiment, the cerium salt is a water-soluble cerium salt.
[0106] As an embodiment, the cerium salt includes one or more of cerium nitrate, cerous nitrate, and cerium chloride.
[0107] As an embodiment, the precipitant includes one or more of alkaline substances, amide compounds, organic acids, and organic amines.
[0108] As an embodiment, the alkaline substance is selected to generate OH after dissolving in water. - of substance.
[0109] As an embodiment, the alkaline substance is selected from one or more of carbonates and bicarbonates.
[0110] As an embodiment, the carbonate is selected from one or more of sodium carbonate, potassium carbonate, and ammonium carbonate.
[0111] As an embodiment, the bicarbonate is selected from one or more of sodium bicarbonate, potassium bicarbonate, and ammonium bicarbonate.
[0112] As an embodiment, the organic acid is oxalic acid.
[0113] As an embodiment, the organic amine is triethylenetetramine.
[0114] As an embodiment, the amide compound is urea.
[0115] The following is a detailed introduction to the preparation method of cerium oxide powder by using urea as a precipitant.
[0116] Example 1
[0117] 200 mL of 0.75 mol / L cerium nitrate aqueous solution was slowly added to 200 mL of 1.5 mol / L urea aqueous solution at 20 mL / s. Ultrasonic mechanical stirring was performed at an ultrasonic frequency of 30 khz and a magnetic stirring speed of 1000 r / min during the whole process and continued until the solution reaction was completed, and then the ultrasonic mechanical stirring was stopped; the reaction system was allowed to stand for 4 h, and then the upper clear liquid was filtered out, the precipitate was washed with deionized water to neutrality, and then washed with anhydrous ethanol, and finally dried at 60 ° C to obtain a pre-product; the pre-product was calcined at 450 ° C for 2 h to obtain a light yellow solid powder, such as Figure 1 As shown, it is labeled as sample C-1.
[0118] The morphology of C-1 samples was detected by scanning electron microscopy. Figure 2 As shown, it can be seen that the C-1 sample is a ball-and-rod mixed type with good dispersion. The particle size of the spherical sample is approximately between 400 and 800 nm, and the particle size of the rod-shaped sample is approximately 4 to 10 μm.
[0119] It should be noted that the prepared samples include both micrometer-scale and nanometer-scale particle sizes, and therefore, are referred to as micro-nano scale in the present invention.
[0120] Example 2
[0121] The steps of this embodiment are basically the same as those of Embodiment 1, except that:
[0122] The concentration of urea aqueous solution was replaced by: 1 mol / L;
[0123] The concentration of the cerium nitrate aqueous solution was replaced with: 0.5 mol / L.
[0124] The morphology of C-2 samples was tested by scanning electron microscopy. Figure 3 As shown, it can be seen that the C-2 sample is a ball-and-rod mixed type with good dispersion. The particle size of the spherical sample is approximately between 400 and 800 nm, and the particle size of the rod-shaped sample is approximately 4 to 10 μm.
[0125] Example 3
[0126] The steps of this embodiment are basically the same as those of Embodiment 1, except that:
[0127] The concentration of urea aqueous solution was replaced by: 0.5 mol / L;
[0128] The concentration of the cerium nitrate aqueous solution was replaced with: 0.5 mol / L.
[0129] The morphology of C-3 samples was detected by scanning electron microscopy. Figure 4As shown, it can be seen that the C-3 sample is a ball-and-rod mixed type with good dispersion. The particle size of the spherical sample is approximately between 400 and 800 nm, and the particle size of the rod-shaped sample is approximately 4 to 10 μm.
[0130] Example 4
[0131] The steps of this embodiment are basically the same as those of Embodiment 1, except that:
[0132] The concentration of urea aqueous solution was replaced by: 0.5 mol / L;
[0133] The concentration of the cerium nitrate aqueous solution was replaced with: 1.5 mol / L.
[0134] The morphology of C-4 samples was tested by scanning electron microscopy. Figure 5 As shown, it can be seen that the C-4 sample is a ball-and-rod mixed type with good dispersion. The particle size of the spherical sample is approximately between 400 and 800 nm, and the particle size of the rod-shaped sample is approximately 4 to 10 μm.
[0135] Comparative Example 1
[0136] The steps of this comparative example are basically the same as those of Example 1, except that:
[0137] 200 mL of 1.5 mol / L urea aqueous solution was replaced with 200 mL of 1.5 mol / L NaOH aqueous solution, and the prepared cerium oxide powder sample was marked as D-1.
[0138] SEM and TEM inspection Figure 6 As shown, the prepared cerium oxide sample has a spherical morphology, a particle size of about 200-400nm, and is severely agglomerated.
[0139] Comparative Example 2
[0140] The steps of this comparative example are basically the same as those of Example 1, except that:
[0141] The urea aqueous solution also contained 0.018 g of citric acid and 2.0 g of PVP. The prepared cerium oxide powder sample was labeled as D-2. SEM and TEM examination showed that Figure 7 As shown, the prepared cerium oxide sample has a rod-like morphology, a particle size of about 100-500 nm, is fragile and has severe agglomeration.
[0142] This specific embodiment will next introduce the composition of the rubber composite material and the method for preparing the rubber composite material using the cerium oxide powder prepared as an antioxidant.
[0143] The present invention provides a composition of a rubber composite material, comprising a ball-and-bat mixed structure cerium oxide material as an antioxidant, and the composition comprises, by mass:
[0144] Raw rubber: 100 parts, reinforcing agent: 40~70 parts, activator: 4~6 parts, plasticizer: 1~3 parts, dispersant: 0.5~2 parts, accelerator: 1~3 parts, vulcanizer: 1~3 parts, antioxidant: 0.5~10 parts.
[0145] As an embodiment, the raw rubber is one of natural rubber, butyl rubber, styrene-butadiene rubber, brominated butyl rubber, chlorinated butyl rubber, chlorosulfonated polyethylene rubber, nitrile rubber, polyacrylate rubber, chloroprene rubber, silicone rubber, and polysulfide rubber.
[0146] In some embodiments, the raw rubber is natural rubber.
[0147] As an embodiment, the reinforcing agent includes an organic, inorganic or metal oxide filler.
[0148] As an embodiment, the reinforcing agent includes one or more of carbon black, resin, short fiber, lignin, graphene, carbon nanotubes, white carbon, kaolin, and mica flakes.
[0149] As an embodiment, the reinforcing agent is carbon black.
[0150] As one embodiment, the active agent is zinc oxide.
[0151] As an embodiment, the plasticizer includes one or more of vaseline, paraffin, pine tar, and fatty acid.
[0152] As an embodiment, the plasticizer is stearic acid.
[0153] As an embodiment, the dispersant includes one or more of vinyl bisstearamide, octadecylamine, and sodium dodecyl sulfate.
[0154] As an embodiment, the dispersant is vinyl bisstearamide.
[0155] As an embodiment, the accelerator includes one or more of benzothiazole disulfide, N-cyclohexyl-2-benzothiazole sulfenamide, N-oxydiethylene-2-benzothiazole sulfenamide, tetramethylthiuram disulfide, and diphenylguanidine.
[0156] As an embodiment, the accelerator includes benzothiazole disulfide and N-cyclohexyl-2-benzothiazole sulfenamide.
[0157] As an embodiment, the mass ratio of benzothiazole disulfide to N-cyclohexyl-2-benzothiazole sulfenamide is 1: (1-3).
[0158] As an embodiment, the vulcanizing agent is selected from one of a sulfur vulcanization system, a phenolic resin vulcanization system, a peroxide vulcanization system, a metal oxide vulcanization system, and a maleimide vulcanization system.
[0159] As an embodiment, the vulcanizing agent includes one of sulfur, dicumyl peroxide, phenolic resin, p-benzoquinone dioxime, and maleimide.
[0160] As an embodiment, the phenolic resin is selected from brominated octylphenolic vulcanized resin.
[0161] As an embodiment, the vulcanizing agent is sulfur.
[0162] The preparation method of the rubber composite material is introduced below through Examples 5 to 10.
[0163] Example 5
[0164] Prepare the following raw materials by weight:
[0165] 100 parts of natural rubber, 58 parts of carbon black, 5 parts of zinc oxide, 2 parts of stearic acid, 1 part of vinyl bisstearamide (EBS), 1.5 parts of N-cyclohexyl-2-benzothiazole sulfenamide (CZ), 0.5 parts of dibenzothiazyl disulfide (DM), 1.8 parts of sulfur, and the C-1 sample prepared in Example 1. Among them, C-1 accounts for 0.5 wt.% in the raw materials.
[0166] The above raw materials were put into an internal mixer for internal mixing, the temperature was controlled at about 65 ℃, and the internal mixing time was controlled at 15 min; the internally mixed materials were thinly passed through an open mixer for 5 times, the roller distance was adjusted to 2 mm, and a mixed rubber was obtained after rolling; the mixed rubber was hot pressed on a flat plate at 140 ℃ and 20 MPa pressure for 30 min to obtain a cerium oxide modified natural rubber composite material, such as Figure 8 As shown, marked as NR-0.5%CeO 2 .
[0167] Example 6
[0168] The steps of this embodiment are basically the same as those of Embodiment 5, except that:
[0169] The cerium oxide modified natural rubber composite material prepared with C-1 accounting for 1 wt.% in the raw materials is labeled as NR-1%CeO 2 .
[0170] Example 7
[0171] The steps of this embodiment are basically the same as those of Embodiment 5, except that:
[0172] C-1 accounts for 2 wt.% in the raw materials, and the prepared cerium oxide modified natural rubber composite is marked as NR-2%CeO 2 .
[0173] Example 8
[0174] The steps of this embodiment are basically the same as those of Embodiment 5, except that:
[0175] C-1 accounts for 3wt.% in the raw materials, and the prepared cerium oxide modified natural rubber composite is marked as NR-3%CeO 2 .
[0176] Example 9
[0177] The steps of this embodiment are basically the same as those of Embodiment 5, except that:
[0178] C-1 accounts for 4wt.% in the raw materials, and the prepared cerium oxide modified natural rubber composite is marked as NR-4%CeO 2 .
[0179] Comparative Example 3
[0180] The steps of this comparative example are basically the same as those of Example 5, except that:
[0181] C-1 accounts for 0wt.% in the raw materials, and the prepared natural rubber composite is marked as NR-0%CeO 2 .
[0182] Comparative Example 4
[0183] The steps of this comparative example are basically the same as those of Example 5, except that:
[0184] 0.5 wt.% of the C-1 sample in the raw material was replaced by 0.5 wt.% of the D-1 sample, and the prepared rubber composite was labeled NR-D-1.
[0185] Comparative Example 5
[0186] The steps of this comparative example are basically the same as those of Example 5, except that:
[0187] 0.5 wt.% of the C-1 sample in the raw material was replaced by 0.5 wt.% of the D-2 sample, and the prepared rubber composite was labeled NR-D-2.
[0188] Example 10
[0189] Prepare the following raw materials by weight:
[0190] 100 parts of natural rubber, 45 parts of carbon black, 5 parts of zinc oxide, 1.5 parts of stearic acid, 1 part of vinyl bisstearamide (EBS), 1.5 parts of N-cyclohexyl-2-benzothiazole sulfenamide (CZ), 0.5 parts of dibenzothiazyl disulfide (DM), 1.5 parts of sulfur, and the C-1 sample prepared in Example 1. Among them, C-1 accounts for 0.5 wt.% in the raw materials.
[0191] The above raw materials were put into an internal mixer for internal mixing, the temperature was controlled at about 65 ℃, and the internal mixing time was controlled at 15 min; the internally mixed materials were thinly passed through an open mixer for 5 times, the roller distance was adjusted to 2 mm, and a mixed rubber was obtained by rolling; the mixed rubber was hot pressed on a flat plate at 140 ℃ and 20 MPa pressure for 30 min to obtain a cerium oxide modified natural rubber composite material.
[0192] Embodiment 11
[0193] Prepare the following raw materials by weight:
[0194] 100 parts of natural rubber, 65 parts of carbon black, 5 parts of zinc oxide, 2 parts of stearic acid, 1 part of vinyl bisstearamide (EBS), 1 part of N-cyclohexyl-2-benzothiazole sulfenamide (CZ), 1 part of dibenzothiazyl disulfide (DM), 2 parts of sulfur, and the C-1 sample prepared in Example 1. Among them, C-1 accounts for 0.5 wt.% in the raw materials.
[0195] The above raw materials were put into an internal mixer for internal mixing, the temperature was controlled at about 65 ℃, and the internal mixing time was controlled at 15 min; the internally mixed materials were thinly passed through an open mixer for 5 times, the roller distance was adjusted to 2 mm, and a mixed rubber was obtained by rolling; the mixed rubber was hot pressed on a flat plate at 140 ℃ and 20 MPa pressure for 30 min to obtain a cerium oxide modified natural rubber composite material.
[0196] Performance testing and analysis
[0197] 1. Aging performance
[0198] The air aging resistance, ozone aging resistance and UV aging resistance of the rubber composite materials prepared in the above Examples 5-9 and Comparative Examples 3-5 were tested, respectively, according to GB / T3512-2014 (hot air accelerated aging and heat resistance test of vulcanized rubber or thermoplastic rubber) at 84 ° C for 48 h, GB / T7762-2014 (static tensile test of vulcanized rubber or thermoplastic rubber for ozone cracking resistance) at 25 ° C, ozone concentration of 100 pphm, elongation of 20% for 48 h, GB / T16585-1996 (artificial weathering aging (fluorescent UV lamp) test method for vulcanized rubber) at an ultraviolet radiation intensity of 0.51 W / m 2 , aging for 48h under the conditions of temperature of 50℃ and humidity of 100%.
[0199] The samples before and after aging were subjected to tensile tests. The tensile test equipment is as follows: Fig. 9 As shown, the tensile parameters are: tensile rate 500 mm / min, and the stress-strain curve before aging is as follows Fig.10 (a) and Fig.11 (a) shows the stress-strain curve after heat-resistant air aging. Fig.10 (b) and Fig.11 (b) shows the stress-strain curve after ozone aging. Fig.10 (c) and Fig.11 (c) shows the stress-strain curve after UV aging. Fig.10 (d) and Fig.11 (d), and the corresponding performance calculation results are shown in Table 1. The improvement effects of rubber composite samples prepared by adding different proportions of cerium oxide on different properties are shown in Table 2.
[0200] Table 1 Performance test results of rubber composite materials
[0201]
[0202] Table 2 Improvement effects of Examples 5 to 9 compared with Comparative Example 3 on different properties
[0203]
[0204] It should be noted that the improvement effects in Table 2 are multiple relationships, that is, the corresponding performance values of a certain embodiment are divided by the corresponding performance values of Comparative Example 3, for example: the improvement effect of tensile strength in heat-resistant air aging performance = 14.28 / 13.57 = 1.05.
[0205] It can be seen from Table 1 and Table 2 that the addition of CeO2 can improve the tensile strength, elongation at break and aging resistance of rubber composites. All three properties show an increase with the addition of CeO2.2 When the content gradually increases, it tends to increase first and then decrease.
[0206] In different embodiments, when 1 wt.% or 2 wt.% CeO is added 2 The tensile strength and elongation at break of the cerium oxide modified rubber composite material reached the maximum value, which is about NR-0%CeO 2 After different types of aging, the retention rates of tensile strength and elongation at break increased by 1.1 to 1.2 times, indicating that the cerium oxide material provided by the present invention has better performance in improving rubber aging. When the content increases to 4 wt%, the tensile strength of the cerium oxide modified rubber composite material decreases, but the elongation at break increases slightly, and the aging performance under heat resistance, ozone resistance and UV resistance also increases slightly. Relatively speaking, adding 2 wt.% CeO 2 Example 7 has relatively better heat aging resistance when adding 1 wt.% CeO 2 Example 6 has relatively better ozone aging resistance and UV aging resistance.
[0207] It is worth noting that in the above embodiments, in the UV aging performance experiment, adding 1 wt.% or 2 wt.% CeO 2 The cerium oxide modified rubber composite material showed a tensile strength retention rate and a break elongation retention rate of more than 100%, making it more suitable for use in ultraviolet environments, such as rubber sealing strips, rubber tubes, rubber conveyor belts, solar panel packaging materials, and other applications that have high requirements on the material's resistance to ultraviolet aging. The reliability and service life in actual use will be greatly improved.
[0208] After the natural rubber composite material provided by the present invention is subjected to hot air aging, ozone aging and ultraviolet aging treatment, the tensile strength retention rate and the elongation at break retention rate can be maintained at more than 70%. Compared with single spherical and rod-shaped cerium oxide as a rubber antioxidant, the serious agglomeration causes most of the cerium oxide to be unable to disperse in the rubber and unable to exert its anti-aging effect. The ball-and-rod mixed cerium oxide of the present invention can further improve the heat air aging resistance, ozone aging resistance and ultraviolet aging resistance of the rubber, and has good dispersibility, a simple preparation method, low cost, and is easy to mass produce.
[0209] 2. Thermal stability
[0210] The thermal stability of Examples 5-8 and Comparative Example 3 was tested using a TGA2050 thermogravimetric analyzer. The test curves are shown in FIG. Fig.12 As shown. It can be seen that Fig.12 (a) TGA curve shows that NR-0%CeO 2One-step decomposition occurs, and the decomposition temperature starts at 330 °C. After adding 0.5 wt.% cerium oxide, the TGA and its first-order derivative curves DTG ( Fig.12 (b)) shifts to a higher temperature, and the decomposition temperature increases by nearly 20 °C. 2 Addition helps to improve the thermal stability of natural rubber composites.
[0211] The above describes the specific embodiments of the present invention. It should be understood that the present invention is not limited to the above specific embodiments, and those skilled in the art may make various modifications or variations within the scope of the claims, which do not affect the essence of the present invention.
Claims
1. A cerium oxide material, characterized in that: The morphology of the cerium oxide material is a ball-and-rod mixed structure, the particle size of the spherical particles is nanometer-level, and the particle size of the rod-shaped particles is micrometer-level, and the spherical particles and the rod-shaped particles are prepared simultaneously during the reaction process; The short diameter of the rod-shaped particles in the cerium oxide material is in the range of 0.5-3 μm, the long diameter is in the range of 4-10 μm, and the aspect ratio is 1:(2.5-10); The particle size of the spherical particles in the cerium oxide material is 400-800 nm; The cerium oxide material is prepared by reacting a cerium salt and a precipitant in an aqueous solution environment to generate a precipitate, extracting the precipitate and calcining it, wherein the cerium salt is a water-soluble cerium salt; the precipitant is urea, and the molar ratio of the cerium salt to the precipitant is 1: (0.3~2).
2. The use of the cerium oxide material according to claim 1, characterized in that: The cerium oxide material is applied to the fields of luminescent materials, polishing agents, ultraviolet absorbers, automobile exhaust purification catalysts, chemical decolorizing agents for glass, radiation-resistant glass, electronic ceramics, and rubber materials.
3. The method for preparing the cerium oxide material according to claim 1, characterized in that: The following steps are involved: The cerium salt and the precipitant are reacted in an aqueous solution environment to generate a precipitate, and the precipitate is extracted and calcined to obtain a cerium oxide material with a ball-and-stick mixed structure, wherein the cerium salt is a water-soluble cerium salt; the precipitant is urea, and the molar ratio of the cerium salt to the precipitant is 1: (0.3~2).
4. The method for preparing the cerium oxide material according to claim 3, characterized in that: The calcination treatment is carried out at a temperature of 450-800°C and for a time of 1-2 h.
5. A rubber composite material composition, characterized in that: The composition includes an antioxidant, which is the cerium oxide material according to claim 1. The composition includes, by weight: Raw rubber: 100 parts, reinforcing agent: 40~70 parts, activator: 4~6 parts, plasticizer: 1~3 parts, dispersant: 0.5~2 parts, accelerator: 1~3 parts, vulcanizer: 1~3 parts, antioxidant: 0.5~10 parts.
6. The rubber composite material composition according to claim 5, characterized in that: It also includes one or more of the following technical features: A. The raw rubber is one of natural rubber, butyl rubber, styrene-butadiene rubber, brominated butyl rubber, chlorinated butyl rubber, chlorosulfonated polyethylene rubber, nitrile rubber, polyacrylate rubber, chloroprene rubber, silicone rubber, and polysulfide rubber; B. The reinforcing agent includes one or more of carbon black, resin, short fiber, lignin, graphene, carbon nanotubes, white carbon, kaolin, and mica flakes; C. The active agent is zinc oxide; D. The plasticizer includes one or more of vaseline, paraffin, pine tar, and fatty acid; E. The dispersant includes one or more of vinyl bisstearamide, octadecylamine, and sodium dodecyl sulfonate; F. The accelerator includes one or more of benzothiazole disulfide, N-cyclohexyl-2-benzothiazole sulfenamide, N-oxydiethylene-2-benzothiazole sulfenamide, tetramethylthiuram disulfide, and diphenylguanidine; G. The vulcanizing agent is selected from one of a sulfur vulcanization system, a phenolic resin vulcanization system, a peroxide vulcanization system, a metal oxide vulcanization system, and a maleimide vulcanization system.
7. A method for preparing a rubber composite material, characterized in that: The raw material is a composition of the rubber composite material according to any one of claims 5 to 6, and the preparation method comprises the following steps: The composition is subjected to a banburying treatment to obtain a banburying rubber; The rubber mix is subjected to a thin pass treatment to obtain a rubber mix; The rubber compound is subjected to a flat plate hot pressing process to obtain the rubber composite material.
8. The method for preparing the rubber composite material according to claim 7, characterized in that: Includes one or more of the following technical features: A. The temperature of the banburying treatment is 60-100°C and the time is 12-15 min; B. The roller distance in the thin pass process is adjusted to 1.5-2.5 mm; C. The temperature during the flat plate hot pressing treatment is 140-180°C, the pressure is 10-20 MPa, and the time is 15-30 min.